Growth-promoting effects of arbuscular mycorrhizal fungus Funneliformis mosseae in rice, sesame, sorghum, Egyptian pea and Mexican hat plant - Zhou, Rong; Raza, Ali; Song, Jueping; Janiad, Sara; Li, Qian; Huang, Miaomiao; Hassan, Muhammad Ahmad (Frontiers in Microbiology, 2025)
Excessive use and overreliance on chemical fertilizers threatens soil health and environmental sustainability, necessitating eco-friendly alternatives like arbuscular mycorrhizal fungi (AMF). The benefits of AMF are well-documented in staple crops, their effects on diverse species—particularly legumes and non-crop models under uniform conditions—remain underexplored, limiting their scalable adoption. This study evaluated Funneliformis mosseae’s role in enhancing growth, nutrient uptake, and stress resilience across five species: rice (Oryza sativa), sesame (Sesamum indicum), sorghum (Sorghum bicolor), Egyptian pea (Sesbania sesban), and the non-crop Kalanchoe daigremontiana. The pot-experiment was conducted in natural open-field conditions (e.g., ambient light, temperature, and humidity) and inoculated plants were analyzed for biomass yield, nutrient concentrations, and physiological parameters to evaluate F. mosseae’s efficacy as a sustainable growth promoter. Inoculation with F. mosseae significantly enhanced plant performance across all species. Rice exhibited a 43% increase in dry biomass, alongside 53% higher phosphorus uptake and 24.5% greater magnesium accumulation. Root development improved markedly, with sesame, sorghum, Egyptian pea, and Mexican hat plants showing root length increases of 66.7, 42.9, 35, and 33.3%, respectively. Biomass gains were consistent: Egyptian pea (29% fresh biomass, 33% dry), sesame (30% fresh, 39% dry), sorghum (36.6% total), and Mexican hat plant (31% fresh, 34% dry). Nutrient uptake surged systemically, including potassium (sesame: 42%, Egyptian pea: 17.8%), calcium (sesame: 54.5%, sorghum: 29.4%), and magnesium (Mexican hat plant: 32.4%, Egyptian pea: 22.5%). Physiologically, photosynthetic rates rose by 21.4–45% (highest in Egyptian pea), stomatal conductance improved by 23.3–71.4% (peak in sesame), and chlorophyll a and b levels increased by 30–39.1% and 44.4–150.8%, respectively, across species. These results suggested that F. mosseae could provide a sustainable, environment friendly substitute for chemical fertilizers, preparing for the future of agriculture, where ecological services such as crop productivity and soil fertility depend on mycorrhizas alongside conventional cultivation practices. Integrating AMF into agricultural systems offers a potential strategy for eco-friendly farming practices that are viable and secure for long-term food security and eco-sustainability.